Chromatographic Studies on Extracts of Ganoderma lucidum - Nahata, Alok; Dixit, Vinod Kumar (Indian Journal of Natural Products, 2022)
Ganoderma lucidum is considered to be a natural medicine that promotes longevity and maintains the vitality of human beings. Its beneficial clinical effects in patients with hepatitis, hyperglycemia, chronic bronchitis, cancer, muscular dystrophy, arteriosclerosis, hypertension, hypercholesterolemia, and leukopenia have been confirmed in pharmacologic studies in recent years. The fruiting bodies, mycelia, and spores have recently received more and more attention not only as home remedies but also as new drug sources. Being an important medicinal mushroom, it was thought necessary to scan the mushroom for its chemical constituents and to work out it’s chromatographic profile via thin layer chromatographic and high-performance thin layer chromatographic approaches. Present work sheds light on the qualitative chemical examination of Ganoderma extracts and their further chromatographic analysis. Standard marker viz., beta-sitosterol was used in the process. Some major phytoconstitents found to be present were triterpenoids and polysaccharides which have been held responsible for most of the pharmacological activities of the mushroom.
Keywords: Ganoderma lucidum; TLC; HPTLC; Phytochemistry; Polysaccharides; Triterpenoids